2012
DOI: 10.3989/cyv.412012
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of different types of coal fly ash in the production of ceramic tiles

Abstract: The influence of varying proportions of different types of fly ash (used in place of feldspar) and different sintering temperatures on the sintered properties of ceramic tile bodies was evaluated. The results indicated that sintering ceramic tiles with a high fly ash content at a high temperature caused a decrease in the properties because of bloating. The ceramic samples containing a higher amount of fly ash that were sintered at low temperature exhibited lower water absorption, larger shrinkage and strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 20 publications
1
13
0
3
Order By: Relevance
“…It is possible to use maximum 20 wt.% of FBC ash in the fly ash-clay mixture. Kockal [95] evaluated the effects of fly ash addition and sintering temperatures on the sintered properties of ceramic tile bodies. The results indicated that incorporating fly ash into the ceramic slurry produced a ceramic body with comparable properties as that of commercial ceramic materials.…”
Section: Ceramic Industrymentioning
confidence: 99%
“…It is possible to use maximum 20 wt.% of FBC ash in the fly ash-clay mixture. Kockal [95] evaluated the effects of fly ash addition and sintering temperatures on the sintered properties of ceramic tile bodies. The results indicated that incorporating fly ash into the ceramic slurry produced a ceramic body with comparable properties as that of commercial ceramic materials.…”
Section: Ceramic Industrymentioning
confidence: 99%
“…Fig. 1 shows the dilatometric curves of the samples; the development of this analysis was performed from room temperature up to 1000 ºC to observe the initial behavior of the material because it is at this temperature range where most of the reactions occur that should be controlled when the material is sintered at high temperatures [12]. All the curves presented the same behavior with slight differences in M0, which presented a curve a little more upwards in comparison with the others.…”
Section: Resultsmentioning
confidence: 78%
“…It was observed that increasing the corundum reduced the expansion, displacing the zone of the first great contraction at higher temperatures and with a lower slope causing a slow and gradual decrease of the dimensions up to 1000 °C, improving the cooking at high temperatures and increasing the structural, mechanical and tribological properties, as is shown later. Furthermore, it is generally known that ceramic materials having lower coefficients of thermal expansion exhibit higher resistance to thermal shock, despite their low ductility [12,15].…”
Section: Resultsmentioning
confidence: 99%
“…De igual manera la porosidad abierta se manifiesta en mezclas cerámicas con adiciones de cenizas de incinerador de biomasa [38], con el que la absorción de agua aumenta, mientras la densidad aparente y la resistencia a la compresión disminuye a mayores adiciones de este residuo, mientras que las mezclas con adición de cenizas de centrales termoeléctricas en reemplazo del feldespato [39], generan un comportamiento contrario, menor absorción de agua, mayor densidad y resistencia a la compresión.…”
Section: Productos Cerámicosunclassified